Referral for Weight Management in Early Intervention in Psychosis - Richard Chater; Priyanka Kaushal (BJPsych Open)
Aims: People with psychosis die, on average, 15–20 years earlier than the general population, with cardio-metabolic syndrome as the biggest contributor to excess mortality. Compounding this, poor concordance with antipsychotic medications is often attributed to weight gain.